2011
DOI: 10.1016/j.virol.2010.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defense is one of the mechanisms by which mosquito cells survive dengue 2 viral infection

Abstract: Dengue viruses (DENVs) generally induce apoptosis in mammalian cells but cause only minor damage in mosquito cells. To find genes involved in determining the cell fate, datasets derived from expressed sequence tags (ESTs) of C6/36 cells with and without infection were established. Of overexpressed genes found in infected dataset, chaperone proteins were validated significantly upregulated in C6/36 cells at 24 hpi. It suggests that DENV-2 in mosquito cells activates the unfolded protein response to cope with en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 54 publications
6
73
0
Order By: Relevance
“…[31][32][33] It is therefore of relevance to determine if VEEV infection will impact insect cells and lead to accumulation of ROS in a similar manner as we observed in U87MG cells. We studied whether infection of mosquito cells with TC-83 would lead to a disruption of mitochondrial function.…”
Section: Veev Infection Results In Loss Of Mitochondrial Membrane Potmentioning
confidence: 73%
See 1 more Smart Citation
“…[31][32][33] It is therefore of relevance to determine if VEEV infection will impact insect cells and lead to accumulation of ROS in a similar manner as we observed in U87MG cells. We studied whether infection of mosquito cells with TC-83 would lead to a disruption of mitochondrial function.…”
Section: Veev Infection Results In Loss Of Mitochondrial Membrane Potmentioning
confidence: 73%
“…It has been demonstrated that in the case of flavivirus infections, infected insect cells show changes in antioxidant mechanisms that decrease the extent of cell death. [31][32][33] It has been demonstrated for Dengue virus that infected mosquito cells mounted a stronger antioxidant response by synthesising antioxidant enzymes (elevation of Glutathione S-transferase activity). 48 Mitochondrial distribution in cells and mitochondrial mobility are essential features of healthy cells.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, this enzyme also reduces O 2 to superoxide, leading to cellular oxidative stress [45]. Previous studies reported the generation of superoxide in mosquito cells during DENV infection [46], and the overexpression of quinone oxidoreductase has been recognized as the major contributor to reactive oxygen species formation [47]. Since the accumulation of this enzyme in the midgut of DENV-infected mosquito was observed [48], the biological interaction between DENV-2 prM protein and A. aegypti NADH-ubiquinone oxidoreductase may be the major contributor in the regulation of the oxido-reduction mechanism to manipulate DENV infection in mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue virus-infected mosquito cells continued growing, implying that an anti-ER stress factor might be involved in the process of viral replication in mosquito cells [25]. Mosquito cells trigger a pathway that protects infected cells from death, which might be how Aedes mosquitoes resist dengue virus infection [26]. Activation of the UPR to cope with ER stress in the early phase of viral infection was shown in various vertebrate cells [27,28].…”
Section: Discussionmentioning
confidence: 99%